BrCl+ elimination from Coulomb explosion of 1, 2-bromochloroethane induced by intense femtosecond laser fields. Issue 55 (7th October 2019) - Wu, Hua; Xue, Yuanxin; Wen, Junqing; Wang, Hui; Bai, Lihua; He, Wanlin; Sun, Ruijuan; Zheng, Wenli
Abstract : Concerted elimination of the molecular ion BrCl + from Coulomb explosion of 1, 2-bromochloroethane was studied theoretically and experimentally. Abstract : By using a dc-slice imaging technique, photodissociation of 1, 2-C2 H4 BrCl was investigated at 800 nm looking for heteronuclear unimolecular ion elimination of BrCl + in an 80 fs laser field. The occurrence of fragment ion BrCl + in the mass spectrum verified the existence of a unimolecular decomposition channel of BrCl + in this experiment. The relative quantum yield of the BrCl + channel was measured to be 0.8%. By processing and analyzing the velocity and angular distributions obtained from the corresponding sliced images of BrCl + and its partner ion C2 H4 +, we concluded that BrCl + came from Coulomb explosion of the 1, 2-bromochloroethane dication 1, 2-C2 H4 BrCl 2+ . With the aid of quantum chemical calculations at the M06-2X/def2-TZVP level, the potential energy surface for BrCl + detachment from 1, 2-C2 H4 BrCl 2+ has been examined in detail. According to the ab initio calculations, two transition state structures tended to correlate with the reactant 1, 2-C2 H4 BrCl 2+ and the products BrCl + + C2 H4 + . In this entire dissociation process, the C–Br and C–Cl bond lengths were observed to elongate asymmetrically, that is, the C–Br chemical bond broke firstly, and subsequently a new Br–Cl chemical bond started to emerge while the C–Cl bond continued to exist for a while. Hence, an asynchronous concerted elimination mechanism was favored for BrCl + detachment.